Olimp leży w Skandynawii, czyli o zawłaszczeniu świata mitów greckich przez XVI- i XVII-wieczne pisarstwo skandynawskie - Szelągowska, Krystyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The classical heritage played a significant role in early modern historical writing, shaping both the message and the narrative form. The inclusion of Greek myths served as a means to support the vision of a glorious past, thereby weaving national history into the broader tapestry of world history. In Scandinavian literature, four mythical stories were particularly influential: those of the Hyperboreans, the Cimmerians, Atlantis, and Odysseus’s travels. Central to this new interpretation was the effort to locate ancient sites and figures within Scandinavian territory.